Inhibitory control of active expiration by the Bötzinger complex in rats - Flor, Karine C. [UNESP]; Barnett, William H.; Karlen-Amarante, Marlusa [UNESP]; Molkov, Yaroslav I.; Zoccal, Daniel B. [UNESP] (Wiley, 2020)
Key points: Contraction of abdominal muscles at the end of expiration during metabolic challenges (such as hypercapnia and hypoxia) improves pulmonary ventilation. The emergence of this active expiratory pattern requires the recruitment of the expiratory oscillator located on the ventral surface of the medulla oblongata. Here we show that an inhibitory circuitry located in the Bötzinger complex is an important source of inhibitory drive to the expiratory oscillator. This circuitry, mediated by GABAergic and glycinergic synapses, provides expiratory inhibition that restrains the expiratory oscillator under resting condition and regulates the formation of abdominal expiratory activity during active expiration. By combining experimental and modelling approaches, we propose the organization and connections within the respiratory network that control the changes in the breathing pattern associated with elevated metabolic demand. Abstract: The expiratory neurons of the Bötzinger complex (BötC) provide inhibitory inputs to the respiratory network, which, during eupnoea, are critically important for respiratory phase transition and duration control. Here, we investigated how the BötC neurons interact with the expiratory oscillator located in the parafacial respiratory group (pFRG) and control the abdominal activity during active expiration. Using the decerebrated, arterially perfused in situ preparations of juvenile rats, we recorded the activity of expiratory neurons and performed pharmacological manipulations of the BötC and pFRG during hypercapnia or after the exposure to short-term sustained hypoxia – conditions that generate active expiration. The experimental data were integrated in a mathematical model to gain new insights into the inhibitory connectome within the respiratory central pattern generator. Our results indicate that the BötC neurons may establish mutual connections with the pFRG, providing expiratory inhibition during the first stage of expiration and receiving excitatory inputs during late expiration. Moreover, we found that application of GABAergic and glycinergic antagonists in the BötC caused opposing effects on abdominal expiratory activity, suggesting complex inhibitory circuitry within the BötC. Using mathematical modelling, we propose that the BötC network organization and its interactions with the pFRG restrain abdominal activity under resting conditions and contribute to abdominal expiratory pattern formation during active expiration observed during hypercapnia or after the exposure to short-term sustained hypoxia.
Keywords: abdominal activity; breathing; GABA; glycine; hypercapnia; hypoxia; pattern